Pengembangan Kualitas dan Rencana Relokasi Proses Produksi Bawang Hitam (Black Garlic) pada UMKM N’Up - Hadi, Yuswono; Valevi, Rendriana Rosa; Noya, Sunday; Ekawati, Yurida (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
The activity this community service aimed to help a small business N’Up to manage their business and increase entrepreneurial spirit. Furthermore, several activities conducted to help UMKM build their marketing strategy and optimize production process by re-locate the factory, re-layout facilities and also analyze their productivity using total productivity model. AHP Method was used to determine the new location of production process. After implementation, they have proper location and facilities and ready to sell their product by using e-commerce.